2020
DOI: 10.1093/infdis/jiaa264
|View full text |Cite
|
Sign up to set email alerts
|

Protective Activity of Programmed Cell Death Protein 1 Blockade and Synergy With Caspofungin in a Murine Invasive Pulmonary Aspergillosis Model

Abstract: Pharmacological immune checkpoint blockade has revolutionized oncological therapies, and its remarkable success has sparked interest in expanding checkpoint inhibitor therapy in infectious diseases. Herein, we evaluated the efficacy of programmed cell death protein 1 (PD-1) blockade in a murine invasive pulmonary aspergillosis model. We found that, compared with isotype-treated infected control mice, anti–PD-1–treated mice had improved survival, reduced fungal burden, increased lung concentrations of proinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…Eight-week-old female BALB/cAnNCrl inbred mice (Charles River Laboratories, weight 20-22 g) were immunosuppressed with 3 intraperitoneal injections of cyclophosphamide (Sigma-Aldrich, 150 mg/kg body weight on days -4 and -1, 100 mg/kg on day +3) and a subcutaneous injection of cortisone acetate (Sigma-Aldrich, 300 mg/kg on day -1), as previously described (16,20). Mice were then infected intranasally with 50,000 spores of R. arrhizus, the most common causative species of IPM in cancer patients (2).…”
Section: Murine Infection Model and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight-week-old female BALB/cAnNCrl inbred mice (Charles River Laboratories, weight 20-22 g) were immunosuppressed with 3 intraperitoneal injections of cyclophosphamide (Sigma-Aldrich, 150 mg/kg body weight on days -4 and -1, 100 mg/kg on day +3) and a subcutaneous injection of cortisone acetate (Sigma-Aldrich, 300 mg/kg on day -1), as previously described (16,20). Mice were then infected intranasally with 50,000 spores of R. arrhizus, the most common causative species of IPM in cancer patients (2).…”
Section: Murine Infection Model and Treatmentsmentioning
confidence: 99%
“…Pathogenic molds were shown to induce checkpoint pathways that can drive immune exhaustion and impair fungal clearance (13,14). Consequently, several invivo studies and clinical case reports suggested a potential of ICIs, especially agents blocking the Programmed Cell Death Protein 1 (PD-1) pathway, as an adjunct treatment for invasive mold infections (14)(15)(16)(17)(18). However, no systematic preclinical studies exist regarding the impact of ICIs on the immunopathology and outcomes of IM.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, immune checkpoint inhibitor therapy is acquiring more attention to infectious diseases [ 38 ]. Indeed, Wurster et al firstly reported that blockade of the PD-1 in vivo (animal model) would contribute to a survival advantage and accelerate Aspergillus fumigatus clearance in lung [ 39 ]. Also, an in vitro study revealed that target PD-L1 would promote a protective immunity to Aspergillus fumigatus [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, further studies are required using mammalian models to evaluate the persistence of ex vivo -stimulated mDCs in vivo , their capacity to migrate to the lymph nodes, as well as their safety and potential immunogenic potential. Future in vivo studies should also include direct comparisons of the feasibility, safety, and efficacy of ex vivo -pulsed mDCs with other potentially promising cell therapeutics (e.g., adoptive T-cell transfer or mold-reactive CAR T-cells) ( 4 , 37 , 38 ) and non-cellular immune enhancement strategies such as immune checkpoint blockade ( 39 ).…”
Section: Discussionmentioning
confidence: 99%